Absolute asymmetric polymerizations in solution needing no physical chiral source. (6th April 2022) - Yin, Guanwu; Namikoshi, Takeshi; Teraguchi, Masahiro; Kaneko, Takashi; Aoki, Toshiki
Abstract: Absolute asymmetric polymerizations, which do not need chiral compounds, are very limited. In addition, they involve spontaneously formed supramolecular compounds, or they need circularly polarized light, and the resulting polymers are often insoluble showing no chiral information at the molecular level. Here we have achieved five kinds of real absolute asymmetric polymerizations of achiral acetylene monomers showing no CD in solution to yield soluble high MW chiral polymers showing CD peaks in solution . These polymerizations did not contain spontaneously formed chiral crystals of monomers or did not use circularly polarized light. A new mechanism we propose here for this new unusual polymerization will give us clues to a better understanding of the reason for the homochirality of our world. Graphical abstract: Image 1 Highlights: AAPs gave soluble high MW polymers showing strong CD in solution . Chiral supramolecules functioned mainly as a chiral ligand of the chiral initiator. Chiral supramolecules formed spontaneously and in-situ during polymerization.